(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Silver nanoparticles were green synthesized using the aqueous extract of Citrus pennivesiculata (Lush.) Tanaka, J. fruit peel. The metallic silver was reduced to silver nanoparticles by the action of secondary metabolites in the fruit peel. The characterization of silver nanoparticles was done by UV-visible spectrophotometry, transmission electron microscopy (TEM), fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). UV-vis spectrophotometry of the silver nanoparticles showed an absorption peak at 435 nm. The TEM analysis showed that the spherical diameter of the particle ranged between 2 to 34 nm. The XRD analysis proved the crystalline nature of the synthesized silver nanoparticles. The FTIR analysis of the synthesized nanoparticles showed the presence of alcohols, phenols, aromatic esters, monosubstituted alkynes, disubstituted alkenes, sulfoxide, amino, and other functional groups. Cytotoxicity and anticancer activity of the green synthesized silver nanoparticles were determined using the mouse fibroblast cell line (L929) and human breast cancer cell line (MCF-7), respectively. The lethal concentration (LC50) of silver nanoparticles on the L929 cell line was found to be 48.521 μg/mL, and that of the MCF-7 cell line was 21.625816 μg/mL. The synthesized silver nanoparticles revealed cytotoxic activity in a dose-dependent manner. The conclusions drawn from this research could be beneficial for nanotechnology-based biomedical applications.